Analysis of Jack the Ripper’s Series of Murders 137 Years Later Using Modern Forensic Tools - Fenyvesi, Csaba; Fábián, Vanessza (Magyar Rendészet, 2025)
The study examines a series of homicides that occurred in London 137 years ago based on a book by Patricia Cornwell, an American forensic lab director. In 2001, the expert conducted a detailed investigation at the original crime scenes and retrieved the case documents related to six victims definitively linked to the perpetrator known as Jack the Ripper. Based on the collected evidence, suspicion arose that the crimes were committed by Walter Sickert, a renowned English painter. The study presents the evidence supporting both personal and material suspicion against him. These findings are compared with milestones in criminalistics and elements of the theoretical pyramid model of criminalistics developed by the authors. The case analysis demonstrates the importance of the forensic “first strike” in leading to a successful investigation. The lack of meticulous crime scene investigation and immediate evidence collection significantly complicates later investigations, even those conducted decades or centuries afterward. At the same time, DNA analysis, widely used in the 21st century, has proven instrumental in solving historical crimes and identifying unknown perpetrators even after 113 years. Overall, the retrospective detection attempt conducted 24 years ago, involving the collection and evaluation of evidence using modern forensic tools, can still provide clues and useful data even 137 years later to advance a previously stalled investigation.